2022
DOI: 10.1212/nxi.0000000000200031
|View full text |Cite
|
Sign up to set email alerts
|

Timing of SARS-CoV-2 Vaccination Matters in People With Multiple Sclerosis on Pulsed Anti-CD20 Treatment

Abstract: Background and ObjectivesOur objective was to investigate cellular and humoral immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination in a cohort of people with multiple sclerosis (pwMS) on pulsed B-cell–depleting treatment (BCDT). In particular, we intended to evaluate a possible association between immune responses and the timing of vaccination under BCDT.MethodsWe conducted a cross-sectional study among pwMS on pulsed BCDT or without disease-modifying treatment after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
6
22
0
Order By: Relevance
“…Attempts to rectify the situation by using more-immunogenic vaccine platforms (e.g., mRNA and viral vector technologies), lowering rituximab dose, or giving additional vaccine doses have not shown promising benefits (32)(33)(34)(35)(36). Previous COVID-19 vaccine immunogenicity studies involving patients with systemic autoimmune diseases, multiple sclerosis, and lymphoma suggested that the key to successful COVID-19 vaccination among rituximab users is to extend the interval between rituximab treatment and vaccination (37)(38)(39). In keeping with the previous studies, we also found a positive correlation between the longer rituximab-to-vaccination intervals and the seroconversion probability of rituximab-exposed IMDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to rectify the situation by using more-immunogenic vaccine platforms (e.g., mRNA and viral vector technologies), lowering rituximab dose, or giving additional vaccine doses have not shown promising benefits (32)(33)(34)(35)(36). Previous COVID-19 vaccine immunogenicity studies involving patients with systemic autoimmune diseases, multiple sclerosis, and lymphoma suggested that the key to successful COVID-19 vaccination among rituximab users is to extend the interval between rituximab treatment and vaccination (37)(38)(39). In keeping with the previous studies, we also found a positive correlation between the longer rituximab-to-vaccination intervals and the seroconversion probability of rituximab-exposed IMDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD20 extended interval dosing could be an opportunity to optimize the timing of the booster to target the period during which there could be B cell repopulation [31,32]. In our cohort, an association between the time of vaccination from the last anti-CD20 infusion or the CD19 + cell number and humoral vaccine response was not demonstrated, unlike other teams [33]. However, our population was very homogeneous because…”
Section: Discussionmentioning
confidence: 69%
“…However, some found suitable immunity after vaccination among rituximab-treated patients ( Takai et al, 2022 ). The protective response following SARS-CoV-2 in rituximab-treated patients is related to the interval between the last rituximab exposure and receiving the vaccine, rituximab concentration, and/or B cell counts in peripheral blood ( Ammitzbøll et al, 2022 ; Spiera et al, 2021 ; Takai et al, 2022 ; Woopen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%